Communication Institutionnelle Et Recrutement Des Étudiants À L’université Félix Houphouët-Boigny De 2004 À 2009 - Sylvain, N’zué Yao (European Scientific Journal, ESJ, 2016)
The Ivorian idiosyncrasy on the market of the French speaking universities in the south of Sahara is characterized by the overabundance of students. That is why we try to understand how corporate advertising contributes to the popularization of the practices of the student “clientele” recruitment process at the university Félix Houphouet-Boigny of Cocody. This work is essentially qualitative with the use of the direct observation technics and the semi-directive interviews with 20 university staffs of student recruitment process. It emerges from it that, on the one hand, the corporate advertising strategies during that operation of recruitment appear in three relation systems: the connections banking on the informal communication through affinities (kinship, friendship), the relations of transactions based on the communication of closeness and the relation of control centered on marketing approach. On the other hand, these strategies establish partly real irregularity sources due to the pouring of thousands (parallel recruitment) of the high school diploma new holders in that public university without taking into account their secondary school performances and the accommodation capacity. This results in the overabundance of students and the worsening of the education quality.